Pendaftaran Tanah Pertama Kali Melalui Pendaftaran Tanah Sistematis Lengkap (PTSL) dengan Alas Hak Jual Beli Secara Adat di Kota Bukittinggi - Angrila Putri; Ferdi, Ferdi; Fendri, Azmi (Universitas Ekasakti, 2024)
Complete Systematic Land Registration (PTSL) is a national strategic project that aims to realize the provision of legal certainty and legal protection of community Land Rights based on the principles of simple, fast, smooth, safe, fair, equitable and open and accountable, so as to improve the welfare and prosperity of the community and the country's economy, as well as reduce and prevent land disputes and conflicts. To accelerate the implementation of registration of all land areas in Indonesia in 2016 a Circular Letter was issued by the Minister of ATR / Head of BPN Number 1756 / 15.I / IV / 2016 concerning Guidelines for the Implementation of Land Registration which is essentially about simplifying the basis of rights for land registration. In this case, for proof of ownership of customary land owned by the Bukittinggi customary law community, some use customary sales and purchase letters. Based on this, the author is interested in conducting research with the formulation of the problem, namely: How is the process of making customary land sales and purchases in Bukittinggi City? How is the process of first land registration through PTSL with customary land sale and purchase rights at the Bukittinggi City Land Office and, How is the process of first land registration through PTSL with customary land sale and purchase rights after the realization of Complete City Mapping in Bukittinggi City. And the purpose of the study is to study and analyze the process of making customary land sales and purchases in Bukittinggi City, to study and analyze the process of first land registration through PTSL with customary land sale and purchase rights at the Bukittinggi City Land Office, and to study and analyze the process of first land registration through PTSL with customary land sale and purchase rights after the realization of Complete City Mapping. The research method is an empirical legal approach method (emphrical legal research), the nature of this research is descriptive. The conclusion is that the PTSL process with the basis of customary land sale and purchase certificates can be used at the Bukittinggi City Land Office and is equipped with a statement of physical control of the land area, and for the land registration process through PTSL after Bukittinggi City is Complete, physical data collection in the form of measuring land areas in the field is no longer carried out, but only legal data collection is carried out.